THE ANALYSIS OF EXTERNAL FACTORS EFFECT ON ONLINE CONSUMER BEHAVIOR TOWARDS ONLINE COSMETICS SHOPPING IN DKI JAKARTA - Rahmatina, Nabila; Suharto, Yulianto (Journal of Business and Management, 2018)
Abstract. As online shopping is getting popular in Indonesia, the number of online shoppers in Indonesia is increasing. The population is dominated by female due to the increasing of purchasing power of female shoppers. With this phenomenon, bigger opportunities occurs for many women necessities industries to rise including online cosmetics industry. Despite the opportunities, the phenomenon also trigger bigger competition. In order to be the one who gives the best services, online cosmetics businesses must understand their consumers behavior. To understand the behavior, it is become a challenge for the businesses since the behavior is changing along the time. This research aim to to identify and analyze the effect of the external factors (perceived risks and trust & security factor) on online consumer behavior towards online cosmetics shopping. Through this research, the researcher also wanted to find out which factor is the most significant among the external factors. This research will be using quantitative approach and the data will be asses using path analysis on AMOS.The research revealed that all the external factors have negative effect and significant influence on online consumer behavior towards online cosmetics shopping. Moreover, time risk is proven to be the factor which gives the most significant effect among the others. The finding also revealed that there are actually linkages between the independent variables. Hopefully, the result finding could be beneficial for the online cosmetics businesses.Keywords: Cosmetics, Perceived Risks, Consumer Behavior, Online Shopping, Trust & Security Factor